2020
DOI: 10.1155/2020/5062506
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Activities of the Methanolic Extract of Cyrtocarpa procera Bark Reduces the Severity of Ulcerative Colitis in a Chemically Induced Colitis Model

Abstract: Cyrtocarpa procera is a plant used in traditional Mexican medicine to treat different gastrointestinal problems. Here, we investigated the effects of a C. procera methanolic extract in DSS-induced colitis mice. Ulcerative colitis (UC) was induced by administering 4% DSS in drinking water to female BALB/c mice. Compared to untreated mice with UC, the treatment group receiving the C. procera extract presented less severe UC symptoms of diarrhea, bleeding, and weight loss. Additionally, colon shortening was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…MDA is another oxidative factor that is increased in ulcerative colitis. In contrast, antioxidants such as GPX and SOD are reduced in this disease [ 78 ]. Motawea et al reported an increase in oxidative factors such as MPO and MDA and a decrease in antioxidants such as GPX and SOD in ulcerative colitis [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDA is another oxidative factor that is increased in ulcerative colitis. In contrast, antioxidants such as GPX and SOD are reduced in this disease [ 78 ]. Motawea et al reported an increase in oxidative factors such as MPO and MDA and a decrease in antioxidants such as GPX and SOD in ulcerative colitis [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that toxic chemicals lead to IBD in animals, various Chinese medicine can treat IBD by improving the survival rate and alleviating the colonic shortening ( Rodriguez-Canales et al, 2020 ). Our results showed that administration of FPE reduced the severity of SDS induced colitis; this statement was supported by survival rate that FPE substantially enhanced the resistance against SDS- derived constant stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining was performed as previously described [ 29 ]. The histological score of colitis in mice was evaluated using three independent parameters as previously described [ 30 ]: extent of injury (0, none; 1, mucosa only; 2, submucosa; 3, transmural), crypt damage (0, none; 1, basal 1/3 damaged; 2, basal 2/3 damaged; 3, almost entire epithelium damaged), and leukocyte infiltration severity (0, none; 1, mild; 2, moderate; 3, severe).…”
Section: Methodsmentioning
confidence: 99%